Influence of social media on the purchase related decisions of tourists in India - Ningombam, Rajesh (Digital Repository of Theses, 2023)
It is necessary to highlight that in recent times several people and tourists in India are using social media platforms in order to get numerous information about traveling. Tourists are getting influenced by Facebooks, Instagram and Twitter these social media platforms in terms of getting more enhanced travel related purchasing decisions. In the tourism industry social media marketing is being implemented. The research includes information from India and also other countries. There are many difficulties arising from the return on investments, once they have adopted and utilized social media for marketing. According to many researchers, there are many difficulties for marketers to measure the revenue. Besides this, many of them don’t know the calculating procedure. Several travel related information such as destination photos, podcasts, videos and blogs are helps tourists in getting effective “tourist behavior” or “tourism behavior”. In this study, the role of Facebook, Instagram and Twitter has been shown in an effective manner. In addition to that, it has been highlighted that some travel related advertisements that are posted by “social media influencers” tourist purchasing decisions. Some social media focused websites have changed their patterns regarding tourists planning to travel, including the path that they purchase and consuming some tourism related products. In terms of understanding these purchasing decisions of several tourists two theories such as “theory of buyer behavior” and “EKB Model” have been used in this study.